Venous thromboembolism in IBD: Increased risk for women in CD?. Issue 2 (June 2019) - Morgan, K.; Boktor, M.; Ford, C.; Pham, L.; Morris, J.D.; Jordan, P.A.; Cvek, U.; Trutschl, M.; Alexander, J.S.
Highlights: Patients with IBD have increased risk of venous thromboembolism. At LSUHSC-S, VTE was 3x more associated with CD than UC. VTE events were more common in white females. African American males had fewer years since IBD diagnosis than white counterparts. Abstract: Although coagulation disturbances have been described in inflammatory bowel disease (IBD), it remains unclear how common venous thromboembolism (VTE) is in IBD, and what factors influence VTE frequency. We evaluated VTE in Crohn's disease (CD) and ulcerative colitis (UC) at LSUHSC-S, a southern US medical center with an approximately equal White: African-American (AA) (1.12:1) patient base. This retrospective study evaluated VTE as a co-morbidity in IBD as a function of age, gender and race based on ICD-10 coding (2011−2015.) Results. Of 276 IBD diagnostic records, 213 were for CD (77.17%) and 63 for UC (22.8%). 52% of the CD patients were white, 42% were AA, and 6% were other. 42% of CD patients were male, with 58% were female. 6.1% (13 patients) of the 213 CD patients had a VTE. Of these 13 CD patients, 9 had active disease and 4 were in remission. 9 of 13 were female and 4 were male, with 5 white patients and 4 A A patients. 63 patients were diagnosed with UC, 3.38-fold fewer cases than CD. 25 UC patients were white, 25 were AA and 13 were in other ethnic groups. Of 63 UC cases, 2 UC patients had a VTE, both with active disease. At our institution, VTE appears to be 3x more frequently associated with CD than UC and was more common in white female patients. The recognition of VTE risk in CD, particularly in women, may be an important observation which may guide therapy and limit potentially life-threatening consequences.